The Role Of Psychological Empowerment As A Mediating Variable Between Perceived Organizational Support And Organizational Citizenship Behaviour In Malaysian Higher Education Institutions - Mohammed Abdulrab; Qais Almaamari; Ali Nasser Al-Tahitah; Osama Isaac; Ali Ameen; Abdul Rahim Zumrah (Lincoln University College, 2024)
Organizational citizenship behaviour is essential in maintaining the pursuit of public universities in offering a quality of education. High sense of organizational citizenship behaviour among employees enables an organization to manage its resources efficiently. This conceptual article will add to the knowledge of the literature by investigating the mediating role of psychological empowerment in the relationship between perceived organizational support and organizational citizenship behaviour in Malaysian Higher Education Institutions. The expected findings will provide a guideline for both policy makers and universities management. The theoretical and practical implications are also discussed.